2005
DOI: 10.1108/07363760510605290
|View full text |Cite
|
Sign up to set email alerts
|

Store visits and information sources among urban Chinese children

Abstract: Purpose -The purpose of this article is to examine how often urban children in mainland China interact with different types of retail shops, how they learn about new products and services, and their attitudes toward different sources of product information. Design/methodology/approach -A survey of 965 urban children ages six to 13 in four Chinese cities, including Beijing, Guangzhou, Nanjing and Shanghai, was conducted in November 2003 to May 2004. Questionnaires were distributed through eight elementary schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
1
17
0
2
Order By: Relevance
“…A survey of more than 1,360 Australian children, conducted by Disney Adventures magazine, recorded 65% of those surveyed accessing the Internet at least once a week, with the majority of these children (69%) having access to the Internet at home (Plaskitt, 2003). A recent study conducted in four urban cities in China, the country with the world's largest population of children, found that 67% have a computer at home and 68% read 'children's newspapers' (Chan, 2005).…”
Section: Food Advertising To Children Via the Internetmentioning
confidence: 99%
“…A survey of more than 1,360 Australian children, conducted by Disney Adventures magazine, recorded 65% of those surveyed accessing the Internet at least once a week, with the majority of these children (69%) having access to the Internet at home (Plaskitt, 2003). A recent study conducted in four urban cities in China, the country with the world's largest population of children, found that 67% have a computer at home and 68% read 'children's newspapers' (Chan, 2005).…”
Section: Food Advertising To Children Via the Internetmentioning
confidence: 99%
“…Diante dos resultados apresentados a H2 corroborou com o que já era afirmado por Chan (2005), os pares (colegas, amigos, entre outros indivíduos do meio de convívio social) também são agentes de socialização importantes. Também foi constatado por Chan (2005) que crianças mais novas adquirem suas normas de comportamento observando seus pais e outros irmãos, enquanto jovens e adolescentes provavelmente olham para seus amigos como fontes pessoais de modelos de consumo.…”
Section: Proporção De Inércia (%)unclassified
“…Também foi constatado por Chan (2005) que crianças mais novas adquirem suas normas de comportamento observando seus pais e outros irmãos, enquanto jovens e adolescentes provavelmente olham para seus amigos como fontes pessoais de modelos de consumo.…”
Section: Proporção De Inércia (%)unclassified
“…technology has reduced the cost and the effort to get information about products (tonta, 2005). thus, the internet has recently become one of the key sources of information about various products for some consumers (Chan, 2005).…”
Section: Background (Product Information Sources)mentioning
confidence: 99%
“…However, Fill (2002) argued that websites provide consumers with information regarding their purchase enquiries. recently, Chan (2005) indicated that the traditional media and the Internet should be used in an integrated way to pump the appropriate messages to the consumers, in particular, to target young consumers. recently, Chan (2005) indicated that the traditional media and the Internet should be used in an integrated way to pump the appropriate messages to the consumers, in particular, to target young consumers.…”
Section: Background (Product Information Sources)mentioning
confidence: 99%